The effectiveness of mathematical learning PBL model based on ethnomathematics sasirangan motives of towards student solving ability - Rahmi Hidayati; Ratna Restapaty (STKIP PGRI Banjarmasin, 2019)
One model of mathematics learning that can be applied to hone problem solving skills is problem based learning (PBL). In this case the problem-solving ability can be collaborated with the existing local culture. The purpose of this study was to determine the effectiveness of ethnomathematics-based PBL models of Sasirangan motifs on students' problem solving abilities as seen from individual completeness (KKM) and classical completeness. The population in this study was VII grade students of SMP Muhammadiyah Banjarbaru in the 2018/2019 school year. The research sample was taken by cluster random sampling technique, where VII E was the experimental class and VII F was the control class. Data collection by the method of documentation, observation and tests. The hypothesis test used is the average test and the proportion test. The results showed that the PBL model based on ethnomathematics of Sasirangan motifs on the effectiveness of students 'problem solving abilities, was shown by the students' problem solving abilities reaching individual completeness above KKM and classical completeness of 75%. Can be seen from the average problem solving ability of students in the experimental class is 83,33 and the control class is 73. Classical completeness for the experimental class was 77% and the control class was 40%.